2020
DOI: 10.1111/afe.12383
|View full text |Cite
|
Sign up to set email alerts
|

The importance of trap type, trap colour and capture liquid for catching Dendrolimus pini and their impact on by‐catch of beneficial insects

Abstract: Dendrolimus pini can be a serious defoliator of pine trees in some European countries. The monitoring of this insect is important, but no single standardized capture technique exists for monitoring purposes. 2 A range of insect trap types (delta sticky, G-trap, Unitrap and cross-vane Unitrap), colours (green, red and white delta traps and yellow and green cross-vane Unitraps) and types of capture liquid (glycol and salt solutions) were tested to determine the most effective trap for D. pini monitoring. Trap co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The results of our studies, and a wide range of available data [ 18 , 27 , 36 , 37 , 38 , 73 , 86 , 98 , 99 , 100 , 101 ] and references therein, indicate that the insect response to different colors is species- and sex-specific and depends largely on their host plants, but also on the coloration of the insects themselves (elytra and body). Our laboratory tests suggest that immature and mature beetles of M. galloprovincialis differ in their color preference; however, this finding should be verified in further studies.…”
Section: Discussionmentioning
confidence: 53%
“…The results of our studies, and a wide range of available data [ 18 , 27 , 36 , 37 , 38 , 73 , 86 , 98 , 99 , 100 , 101 ] and references therein, indicate that the insect response to different colors is species- and sex-specific and depends largely on their host plants, but also on the coloration of the insects themselves (elytra and body). Our laboratory tests suggest that immature and mature beetles of M. galloprovincialis differ in their color preference; however, this finding should be verified in further studies.…”
Section: Discussionmentioning
confidence: 53%
“…Our overall trap performance demonstrated that Delta traps provided similar results, but at certain periods of our monitoring season, red traps performed better than the white ones. Several studies have shown that trap color is a critical parameter that determines trap performance for many moth species [30,31,34]. For the pine processionary moth, Thaumetopoea pityocampa (Denis & Schiffermüller) (Lepidoptera: Thaumetopoeidae), it has been found that white-and yellow-colored traps were more effective for the capture of adults when these traps had been placed in pine trees [35].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of collected insects is thus influenced by the color of the trap and its position. Some studies have shown that the effectiveness of colored traps lies in the ability of insects to detect them [23,24] . Also showed that yellow traps are more attractive to the majority of insects due to their trichromatic vision.…”
Section: Discussionmentioning
confidence: 99%